2022
DOI: 10.1177/17474930211064754
|View full text |Cite
|
Sign up to set email alerts
|

HARM revisited: Etiology of subarachnoid hyperintensities in brain FLAIR MRI

Abstract: Background: The hyperintense acute reperfusion marker (HARM) describes a phenomenon with a hyperintense signal in the subarachnoid space in Fluid-Attenuated Inversion Recovery (FLAIR) magnetic resonance imaging (MRI) sequences, presumably based on blood–brain barrier breakdown in acute stroke with reperfusion. However, this imaging phenomenon was described in other medical conditions. Aim: Determination of the prevalence and associated clinical findings of this phenomenon in a large sample of patients with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…3 A study showed that, when more than 20,000 brain magnetic resonance imaging (MRI) scans were examined, the HARM sign was a rare finding identified in only 0.35% of the scans. 4 However, the HARM sign was observed in 83% of cases of subacute strokes and 10% of TIA cases, indicating that the HARM sign can confirm a cerebral ischemic insult. 5,6 In terms of clinical significance, the HARM sign correlates with hemorrhagic transformation and parenchymal hemorrhage, and it is associated with worse clinical outcomes of stroke.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…3 A study showed that, when more than 20,000 brain magnetic resonance imaging (MRI) scans were examined, the HARM sign was a rare finding identified in only 0.35% of the scans. 4 However, the HARM sign was observed in 83% of cases of subacute strokes and 10% of TIA cases, indicating that the HARM sign can confirm a cerebral ischemic insult. 5,6 In terms of clinical significance, the HARM sign correlates with hemorrhagic transformation and parenchymal hemorrhage, and it is associated with worse clinical outcomes of stroke.…”
Section: Introductionmentioning
confidence: 97%
“…3 A study showed that, when more than 20,000 brain magnetic resonance imaging (MRI) scans were examined, the HARM sign was a rare finding identified in only 0.35% of the scans. 4 However, the HARM sign was observed in 83% of cases of subacute strokes and 10% of TIA cases, indicating that the HARM sign can confirm a cerebral ischemic insult. 5,6…”
Section: Introductionmentioning
confidence: 97%
“…The phenomenon can be a sign of pathologies of the subarachnoid space and/or vessel wall permeability. (Althaus et al, 2022;Stuckey et al, 2007) In cerebral amyloid angiopathy (CAA), subarachnoid CSF hyperintensities on non-contrast 1.5T (T) or 3T FLAIR MRI are often considered a sign of acute convexity subarachnoid hemorrhage (cSAH): acute bleeding from the leptomeningeal vessels into the subarachnoid space. (Calviere et al, 2016) It is hypothesized that (repeated episodes of) cSAH can lead to cortical superficial siderosis (cSS), a hallmark hemorrhagic neuroimaging marker of CAA and one of the strongest predictors for intracerebral hemorrhage (ICH).…”
Section: Introductionmentioning
confidence: 99%